Tradução comentada de A sentimental Journey de Laurence Sterne - Freitas, Luana Ferreira de (2007)
This study will look at the translation of Laurence Sterne’s A Sentimental Journey and examine certain translational issues arising from the narrative. These include the oscillation between sentimental and humorous elements and the fine line that separates them throughout the novel, use of irony, parody, and also translational strategies adopted by the author, and by others in previous translations of the work in Brazil.